Haplotyping by CRISPR-mediated DNA circularization (CRISPR-hapC) broadens allele-specific gene editing. Issue 5 (16th January 2020) - Yu, Jiaying; Xiang, Xi; Huang, Jinrong; Liang, Xue; Pan, Xiaoguang; Dong, Zhanying; Petersen, Trine Skov; Qu, Kunli; Yang, Ling; Zhao, Xiaoying; Li, Siyuan; Zheng, Tianyu; et al.
Abstract: A llele-s pecific p rotospacer a djacent m otif (asPAM )-positioning SNPs and CRISPRs are valuable resources for gene therapy of dominant disorders. However, one technical hurdle is to identify the haplotype comprising the disease-causing allele and the distal asPAM SNPs. Here, we describe a novel CRISPR-based method (CRISPR-hapC ) for haplotyping. Based on the generation (with a pair of CRISPRs) of extrachromosomal circular DNA in cells, the CRISPR-hapC can map haplotypes from a few hundred bases to over 200 Mb. To streamline and demonstrate the applicability of the CRISPR-hapC and asPAM CRISPR for allele-specific gene editing, we reanalyzed the 1000 human pan-genome and generated a high frequency asPAM SNP and CRISPR database (www.crispratlas.com/knockout ) for four CRISPR systems (SaCas9, SpCas9, xCas9 and Cas12a). Using the huntingtin ( HTT ) CAG expansion and transthyretin ( TTR ) exon 2 mutation as examples, we showed that the asPAM CRISPRs can specifically discriminate active and dead PAMs for all 23 loci tested. Combination of the CRISPR-hapC and asPAM CRISPRs further demonstrated the capability for achieving highly accurate and haplotype-specific deletion of the HTT CAG expansion allele and TTR exon 2 mutation in human cells. Taken together, our study provides a new approach and an important resource for genome research and allele-specific (haplotype-specific) gene therapy.